Optimalisasi Rute Dan Biaya Distribusi Menggunakan Metode Saving Matrix Dan Metode Traveling Salesman Problem (Tsp) Pada Depot Air Minum Splazz - Faizal zulkarnain; Suseno Suseno (CV. ALIM'SPUBLISHING, 2024)
Splazz drinking water depot is a refill drinking water depot and drinking water supplier in the Yogyakarta area which has a distribution/delivery route for drinking water to consumers in several different locations. The distribution carried out does not take into account optimal routes so that the costs incurred in distribution are not optimal. By Therefore, research was carried out at the Splazz drinking water depot to optimize routes and costs for distributing drinking water to consumers using the saving matrix method and the branch and bound method. The initial route for the distribution/delivery of drinking water carried out at depots based on days from the data collected shows a total distance of 66.6 Km to 35 delivery points. Processing the data using two different methods resulted in a route saving of 16 - 18% of the delivery distance with a total distance savings of 54.9 Km for the saving matrix method and 55.8 Km for the branch and bound method, the distribution vehicle used uses a modified motorbike with a carrying capacity of 5 gallons. Then calculate the amount of cost savings after saving the distance on the distribution/delivery routes, resulting in fuel cost savings of 16 – 17%.